Technological Aspects of Bridging the Gap Between Cell-Based Food and Conventional Meat - Cheorun Jo; Hyun Young Jung; Jean-François Hocquette; Marie-Pierre Ellies-Oury1; Minsu Kim; Sghaier Chriki (Meat and Muscle Biology)
Cell-based food, including cultured meat, introduces an innovative complement to our dietary options, introducing cellular agriculture and tissue engineering on the meat market together with traditional livestock farming. Originating from medical tissue cultivation techniques, this approach is now tailored for food production, prioritizing cost-effectiveness, palatability, and resource efficiency. As technology strives to efficiently upscale production, consumer acceptance stands as a key factor in adopting this new protein source. This review explores advances in cultivating muscle and fat tissues in vitro, emphasizing the importance of achieving muscle maturity, innovating scaffolds, and optimizing media composition to closely replicate the qualities of meat. It also addresses quality assessments of cultured meat based on its texture, nutritional content, and flavor. A concise examination of consumer perceptions reveals that acceptance is influenced by a blend of cultural, psychological, and social factors, balancing the positive potential outlook on cultured meat’s benefits for society, the environment, and animal welfare against concerns about its unnaturalness, uncertainty, and safety. Demographic trends suggest higher acceptance among younger, well-educated and urban individuals, contrasting with reservations from those more familiar with the traditional meat sector. Addressing these varied viewpoints is essential for a better understanding of public acceptance if cultured meat is effectively introduced into our future food systems. As media interest in this alternative is still high, aligning technological developments with consumer expectations is crucial for the potential market introduction of cultured meat.